The Influence of Service Quality on Customer Loyalty at Ibis Hotel Bandung - Afifa Mukhlis, Ervie Nur; Nurarifian, Muhammad Chairully; Agustian, Deryl; Syafrilyudin, Rafli; Hidayatullah, Tubagus; Susilawati Sugiana, Neng Susi (LPKIA, 2025)
This study aims to analyze the influence of service quality on customer loyalty at Ibis Hotel Bandung. The hospitality industry is highly competitive, and maintaining customer loyalty is crucial for business sustainability. Service quality is considered a key factor influencing customer decisions to repurchase and recommend hotel services to others. This research uses a quantitative method with a survey approach, involving 100 customers who have stayed at Ibis Hotel Bandung. Data were collected through questionnaires measuring five dimensions of service quality: tangibles, reliability, responsiveness, assurance, and empathy. The data were analyzed using multiple linear regression to determine the significance of each dimension’s effect on customer loyalty.The results show that service quality significantly influences customer loyalty at Ibis Hotel Bandung. Among the dimensions, reliability and assurance have the highest positive impact, indicating that customers value consistent service performance and the confidence provided by hotel staff. Tangibles, such as cleanliness and room facilities, also contribute to loyalty, though to a lesser extent. Responsiveness and empathy were found to positively affect loyalty by creating comfort and trust in customers during their stay. These findings imply that Ibis Hotel Bandung must continuously maintain and improve its service quality, especially in ensuring reliable and assured services to increase customer retention and recommendations. This study contributes to the hotel management literature by reaffirming that excellent service quality is a strategic asset in building and sustaining customer loyalty in the hospitality industry.